Hume, Mach e Skinner: a explicação do comportamento - Laurenti, Carolina (Universidade Federal de São Carlos, 2004)
Radical behaviorism was presented as the philosophy of science of human behavior. This has important consequences. One of them has to do with questions regarding scientific explanation. The present essay essentially deals with the following question: what is the model of explanation of radical behaviorism? Some characteristics of the explanation model of behavior are examined, based on a discussion of the ideas of Skinner and two others philosophers of science, to wit, David Hume and Ernst Mach. Hume offers a logical-empirical critique of the concept of causality as necessary connection, by arguing that causal relations can not be demonstrated on the basis of statements of fact. Moreover, experience does not furnish the necessary causal link between cause and effect. He concludes the human knowledge deals solely with constant relations. This critique was taken over by Skinner by way of Mach s functional descriptivism . Mach s substitution of the concept of cause by that of functional relations, and its consequent distinction between scientific explanation and causal explanation is based on Hume s critique. One might also argue that Mach advances on Hume s critique by asserting that the world is, in principle, probabilistic. Skinner, from the beginning, offered an interpretation of behavioral theory as description in accordance with Mach s philosophy of science. Accordingly, he limited himself to explaining behavior in terms of functional relationships. However, it is argued that the explanation of behavior is not only the discovery of functional relations. Skinner does not comply with the restrictions of descriptivism when he offers an interpretation, beyond the bounds of mere functional relations, of the origin of behavior, as is the case with philogenetic behavior and with cultural practices. Accordingly, interpretation is included in radical behaviorism s explanatory system. In this way, the theory of behavior, without rejecting descriptivism, may be associated with a version of scientific instrumentalism. This is done via Mach in a somewhat surprising way. Mach s emphasis on the notions of scientific concept and hypothesis leads us to a kind of reticent instrumentalism which emerges as a reaction to the realist view of theories. As a version of scientific instrumentalism, the theory of behaviorism can be seen as pragmatic, and so radical behaviorism enters the field of ethics. The alliance of descriptivism and instrumentalism rule out realist interpretations of the theory of behavior. A reading of Skinner s theory from the perspective of the philosophical works of Hume and Mach also weaken the association of radical behaviorism with the metaphysical determinism. It is concluded that the model of selection by consequences is a functional, instrumental and probabilistic, rather than causal, way of explaining behavior.
Keywords: Behaviorismo (Psicologia); Causalidade; Instrumentalismo (Filosofia); Probabilismo; Descritivismo; Radical behaviorism; Explanation; Causality; Descriptivism; Instrumentalism; Probabilism; CIENCIAS HUMANAS::FILOSOFIA